Maternal transfer of androgens in eggs is affected by food supplementation but not by predation risk. (26th February 2016) - Morosinotto, Chiara; Thomson, Robert L.; Ruuskanen, Suvi; Korpimäki, Erkki; Lehikoinen, Esa; Möstl, Erich; Laaksonen, Toni
Abstract : Mothers may affect the future success of their offspring by varying allocation to eggs and embryos. Allocation may be adaptive based on the environmental conditions perceived during early breeding. We investigated the effects of food supplementation and predation risk on yolk hormone transfer in the pied flycatcher Ficedula hypoleuca . In a food supplementation experiment, females were food‐supplemented prior to and during egg‐laying and androgen concentrations were measured throughout the laying order. Predation risk was investigated in three different studies combining both correlative data, where flycatchers bred in close proximity to two different predator species that prey upon adult flycatchers (either Tengmalm's owl Aegolius funereus or pygmy owl Glaucidium passerinum ), and an experimental manipulation, where flycatchers were exposed to cues of a nest predator (least weasel Mustela nivalis ). Females receiving food supplementation laid eggs with lower concentrations of androstenedione (A4) than females not receiving food supplements. Yolk testosterone (T) concentration showed the same pattern but the difference was not statically significant. Testosterone (but not A4) concentration increased within clutches, from the first to the last egg, independently of the food supplementation. Females breeding under high predation risk did not differ from control females in their yolk androgen levels (A4, T or progesterone). However, concentrations of A4 tended to be lower in the proximity of pygmy owls, which could indirectly increase offspring survival after fledging. Food supplementation during egg‐laying seems to have a stronger impact on maternal transfer of androgens than predation risk. Food availability and predation risk could differentially affect the trade‐offs of androgen allocation for the offspring when raised in good vs. dangerous environments.